Monitoramento eletrônico de presos e cidadania - Desimone, Fabio Fernandes (2013)
The present work has as central subject the electronic monitoring of prisoners as a form of citizenship exercise in the Brazilian reality. For that, we made a research concerning the historical and conceptualization of citizenship in Brazil, the initial and basic concepts on the punishment by confinement and the proper treatment of the prisoners in the past and the present, going through the main constitutional principles of the imprisoned person. We made a wide approach on the functioning, normalization and hypothesis of current application on the law, the aspect of social insertion of the individual, and the advantages, disadvantages and legal limits of such electronic device. We developed deep research on the international experience about the electronic monitoring of prisoners, and the impact on the Brazilian reality as a new modality of exercising of citizenship.